A Descriptive Study on the Students’ Perception Toward the Use of Board Race Game in Learning English at the Eleventh Grade of SMK PGRI 1 Giri Banyuwangi in the 2022/2023 Academic Year - Dwi yuli yanti; Wulan Wangi; wageyono (LUNAR, 2025)
Perceptions are the results of information which are expressed to other people who have different meanings in each human brain. The purpose of this research is to determine students’ perceptions of the use of the Board Race Game in learning English. This research used method research such as descriptive quantitative research. There were  52 students as respondents of a senior high schools on the eleventh grade at SMK PGRI 1 Giri Banyuwangi. The purposive sampling was one of the techniques used in this research. To find out the perceptions on the use Board Race Game in Learning English, the data collection method was done by filling out the questionnaire. Related to the result of research of the students’ perceptions on the eleventh grade at SMK PGRI 1 Giri Banyuwangi is a good category with overall percentage 78%. The researcher suggests that English teachers use the Board Race Game as a learning method. Through Games, English teachers can deliver the materials easily and creatively